2016
DOI: 10.1186/s12889-016-3424-z
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of couples’ voluntary HIV counseling and testing: a comparison of influence networks in Rwanda and Zambia

Abstract: BackgroundMany African adults do not know that partners in steady or cohabiting relationships can have different HIV test results. Despite WHO recommendations for couples’ voluntary counseling and testing (CVCT), fewer than 10 % of couples have been jointly tested and counseled. We examine the roles and interactions of influential network leaders (INLs) and influential network agents (INAs) in promoting CVCT in Kigali, Rwanda and Lusaka, Zambia.MethodsINLs were identified in the faith-based, non-governmental, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Like our review, a recent consensus statement supporting safer conception and pregnancy for couples living with HIV found that access to SCS is limited by stigma toward HIV affected couples having children and that this stigma limits provision of safer conception services [75]. Increasing community education about SCSs via community health worker networks may help increase acceptability for previously unfamiliar conception strategies and reduce community-, provider-, or family-level stigma around pregnancy in HIV affected couples, as was accomplished with increasing community knowledge and acceptance of HIV testing [76, 77] and couples’ HIV counseling and testing [7880]. …”
Section: Discussionmentioning
confidence: 99%
“…Like our review, a recent consensus statement supporting safer conception and pregnancy for couples living with HIV found that access to SCS is limited by stigma toward HIV affected couples having children and that this stigma limits provision of safer conception services [75]. Increasing community education about SCSs via community health worker networks may help increase acceptability for previously unfamiliar conception strategies and reduce community-, provider-, or family-level stigma around pregnancy in HIV affected couples, as was accomplished with increasing community knowledge and acceptance of HIV testing [76, 77] and couples’ HIV counseling and testing [7880]. …”
Section: Discussionmentioning
confidence: 99%
“…4244 Social Norms Theory highlights the role of community and peer influence in changing health behaviors, and studies have shown that normalizing behaviors like HIV testing through community promotions can decrease stigma and increase uptake. 45,46 Influential network leaders (INLs) were selected from the health care, religious, nongovernmental/community-based, and private sectors.…”
Section: Introductionmentioning
confidence: 99%
“…The highest volume clinics were located in neighborhoods that had previously hosted a neighborhood randomized control trial of CVCT promotion (NIMH R0166767; 2003–2007) and/or other ZEHRP-sponsored work involving promotion and provision of CVCT from the late 1990’s onward [ 4 , 15 – 18 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beginning in 2008, ZEHRP trained government clinic counselors and health promoters in 25 clinics in Lusaka (N = 12) and Ndola (N = 13) to promote and provide CVCT and paid overtime to off-duty clinic staff to offer these services on weekends when the clinics were not congested. In addition to periodic radio programs, promotions were carried out in the community by District Clinic Promoters (DCP) affiliated with the clinics, and by Influence Network agents (INA) affiliated with ZEHRP [ 5 , 21 , 22 ]. In addition, clinic nurses and counselors promoted CVCT among ANC and VCT clients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation